NALISIS PEMAHAMAN PENDIDIKAN SEKS PADA PESERTA DIDIK MELALUI PEMBELAJARAN AGAMA DAN OLAHRAGA DI SDK 143 BHAKTYARSA KECAMATAN ALOK TIMUR KABUPATEN SIKKA - Hero, Hermus (Universitas Islam Balitar, 2019)
This research aims at investigating teachers’ methods in teaching religion and sport related to sexuality. Kind of data used in this study was qualitative data. Qualitative data is kind of data that is written in the form of words. Qualitative data in this study included overview of learning process of religion and sport subjects concerning sex education. Sex education is taught in SDK 143 Bhaktyarsa through learning process of religion and sport via learning materials containing of sexuality. When explaining either religion or sport materials, teachers adopted pictures and simple language to make students more understand the materials.